PENGARUH DISIPLIN TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN PULAU-PULAU TERSELATAN KABUPATEN MALUKU BARAT DAYA - Nova Ratumaly; Stenly Ronaldo Titioka (P3M Politeknik Negeri Ambon, 2023)
Researchers conducted preliminary research at the Pulau-Selatan Island District Office, researchers found problems such as lack of time discipline, lack of responsibility in carrying out work, lack of determination and speed in work so that it affected discipline which led to decreased work performance. The purpose of this study was to determine the effect of work discipline on the work performance of employees at the Terselatan Islands District Office, Southwest Maluku Regency. Discipline is a feeling of obedience to the rules, including doing certain work that is the responsibility so as to achieve the expected performance. Good discipline will improve the performance of good employees.The data used in this study are primary data and data management techniques using validity tests, reliability tests, partial tests (t) and simple regression analysis techniques with the independent variable namely discipline (X) as measured using indicators of time discipline, regulatory discipline and responsibility discipline. responsibility and the dependent variable, namely employee performance (Y), which is measured using indicators of quality, quantity, responsibility, cooperation, and initiative. Based on the results of the simple linear regression test, it shows the equation Y = 19.938 + 0.523X.From the results of discipline, it has a positive and significant effect on employee performance at the Pulau-Selatan District Office, which means that when there is an increase in the value of discipline, it will increase employee performance, and vice versa, this means that the District Office of the Pulau-Selatan Islands must increase discipline so that performance employees also increased.